Hubungan Peran Orang Tua Dengan Perilaku Jajan Tidak Aman Pada Anak Usia Sekolah Dasar Di RW 006 Parigi Lama Pondok Aren Tangerang Selatan - Pasaribu, Sondang Deri Maulina; Komalasari, Oom; Suheti, Suheti; Amelia Putri, Ristina (Jurnal Kesehatan STIKes IMC Bintaro, 2023)
Introduction: Snacks are one of the foods favored by children. Children and snacks are two things that cannot be separated. One of the factors of this snack habit can worsen the nutritional state of children. Because children are often wrong and do not really understand in choosing snacks, especially if they are not guided by their parents. The role of parents is very important in the process of forming behavior in their children.The purpose of the study: to determine the "Relationship of the Role of Parents with Unsafe Snacking Behavior in School Age Children in RW 006 Parigi Lama Pondok Aren, South Tangerang. Methods: This research is a type of research in this writing is a descriptive analytic method using a cross sectional approach. Using non probability sampling method with quota sampling technique. The sample of this research is parents who have elementary school children which was held in January 2022 as many as 40 respondents. This study used a questionnaire about the role of parents and snacking behavior. Research Results: Based on the results of the analysis using the Chi-Square test, a p-value of 0.002 was obtained, which means that there is a relationship between the role of parents and unsafe snacking behavior in school-age children in RW 006 Parigi Lama Pondok Aren, South Tangerang. Suggestion: it is hoped that parents can implement healthy eating behavior for school-age children and add insight to parents to pay attention to snack consumption behavior in children in the home and school environment. So that it can minimize the risk of unwanted disease in children in the future and children can distinguish between safe and unsafe foods for consumption.